Demographic Development of Post-Conflict Societies: the Experience of the Countries of the Former Yugoslavia - Гудзеляк, Ірина (Київський національний університет імені Тараса Шевченка, 2024)
The article shows the demographic losses of the states of the former Yugoslavia in the wars of the 1990s and analyzes the trends of the post-war demographic development of Croatia, Bosnia and Herzegovina, Serbia, Montenegro, North Macedonia, Slovenia, and the partially recognized state of Kosovo. Before the start of the wars, the second demographic transition was largely completed in these countries, and the birth rate approached the average European value. There was no significant reduction in the total birth rate in the countries of the Balkan region during armed conflicts. Only in Kosovo and Bosnia and Herzegovina, there was a noticeable decrease in the number of births due to large migratory losses of reproductive cohorts. The impact of the war was manifested in the accelerated transformation of the age-related birth rate, there was a decrease in the early birth rate against the background of an aging motherhood. It was established that in the post-war societies of the Balkan region, except Serbia, there was no compensatory increase in the birth rate. The birth rate in the countries of the former Yugoslavia changed synchronously with those European states that experienced deep economic crises or geopolitical transformations, in particular, joined the EU. Structural and demographic transformations in post-conflict societies are studied. It was found that during the war, the rate of decline in the share of the child population and the rate of demographic aging were higher than the European average. The long-term dynamics of the age structure of the population of the modern post-conflict countries of the former Yugoslavia do not differ in the main parameters from other European countries. It was established that the main factor in reducing the population of the region is forced external migration. The largest specific weight of emigrants from the number of permanent population is in Kosovo and Bosnia and Herzegovina. In these countries, unresolved ethnopolitical problems destabilize the development of society in general, negatively affect the processes of natural reproduction, and act as a deterrent to the return of migrants. Taking into account the analogies of the post-conflict societies of the Balkan region, as well as taking into account the crisis parameters of the demographic situation before the full-scale war of 2022, the scenarios of the demographic development of Ukraine are built. They are due exclusively to probable migration trends. Optimistic and pessimistic scenarios of the demographic development of Ukraine are determined by several external and internal factors. Recommendations regarding the basic principles of the policy of re-emigration of Ukrainian refugees have been provided.

У статті показано демографічні втрати держав колишньої Югославії у війнах 1990-х років та проаналізовано тенденції повоєнного демографічного розвитку Хорватії, Боснії і Герцеґовини, Сербії, Чорногорії, Північної Македонії, Словенії та частково визнаної держави Косово. До початку воєн в цих країнах в основному завершився другий демографічний перехід, рівень народжуваності наблизився до середньоєвропейського значення. Суттєвого скорочення сумарного коефіцієнта народжуваності в країнах Балканського регіону упродовж збройних конфліктів не було. Лише в Косово та Боснії і Герцеґовині виявлено помітне зниження кількості народжених унаслідок великих міграційних втрат репродуктивних когорт. Вплив війни проявився у пришвидшеній трансформації повікової народжуваності, відбувалося зниження ранньої народжуваності на тлі постарішання материнства. Встановлено, що у поствоєнних суспільствах Балканського регіону, за винятком Сербії, не простежувалося компенсаційного зростання народжуваності. Рівень народжуваності в країнах колишньої Югославії змінювався синхронно з тими європейськими державами, які пережили глибокі економічні кризи, або геополітичні перетворення, зокрема вступили до ЄС. Досліджено структурно-демографічні трансформації у постконфліктних суспільствах. Виявлено, що під час війни темпи зниження частки дитячого населення і темпи демографічного старіння були вищими від середньоєвропейських. Довгострокова динаміка вікового складу населення сучасних постконфліктних країн колишньої Югославії не відрізняється за головними параметрами від інших країн Європи. Встановлено, що головним фактором скорочення кількості населення регіону є вимушена зовнішня міграція. Найбільша питома вага емігрантів від чисельності постійного населення є в Косово та Боснії і Герцеґовині. В цих країнах нерозв’язані етнополітичні проблеми дестабілізують загалом розвиток суспільства, негативно впливають на процеси природного відтворення та виступають стримуючим чинником повернення мігрантів. З урахуванням аналогій постконфліктних суспільств Балканського регіону, а також беручи до уваги кризові параметри демографічної ситуації до повномасштабної війни 2022 року, побудовано сценарії демографічного розвитку України. Вони обумовлені виключно ймовірними міграційними тенденціями. Оптимістичний і песимістичний сценарії демографічного розвитку України визначаються низкою зовнішніх і внутрішніх чинників. Надано рекомендації щодо засадничих принципів політики рееміграції українських біженців.
Демографічний розвиток постконфліктних суспільств: досвід країн колишньої Югославії
Keywords: population; demographic development; age structure; migrations; war; post-conflict society; населення; демографічний розвиток; вікова структура; міграції; війна; постконфліктне суспільство